An integrative literature review on the success of accounting information systems and its impact on the ability to manage crises / Mahmoud Hany Mahmoud Dalloul, Zuraeda Ibrahim and Sharina Tajul Urus - Mahmoud Dalloul, Mahmoud Hany; Ibrahim, Zuraeda; Tajul Urus, Sharina (Faculty of Accountancy, 2019)
Much have been written about Accounting Information Systems (AIS), users’ satisfaction and its impact on the ability to manage crises. However, many issues remain unresolved. The purpose of this integrative literature review is to summarize critique and synthesize past studies. First, contributions of past researchers on AIS and users’ satisfaction are presented. Then followed by a brief discussion on previous empirical studies related to AIS and crises management. This provides an opportunity to investigate previously unexplored research settings; identify the gaps where research can be extended; and assist in identifying all potential attributes that could give significant contribution to the literature related to the AIS.